Implementation of Think–Pair–Share–Based Cooperative Learning in Enhancing Social Skills and Conceptual Understanding in Islamic Religious Education - Muhammad Kholilul Rohman; Fathur Rohman (Journal of Islamic Education Research, 2025)
This study addresses the limited empirical research on cooperative learning in Islamic Religious Education, particularly within vocational secondary school contexts. The purpose of this study is to analyze the implementation of Think–Pair–Share–based cooperative learning and examine its contribution to enhancing students’ social skills and conceptual understanding of fiqh, especially the topic of riba in debt transactions. A qualitative case study design was employed at SMK Sadamiyyah, involving classroom observations, semi-structured interviews, and learning documentation with eight purposively selected participants. Data were analyzed thematically through systematic processes of transcription, data reduction, coding, categorization, and interpretive analysis, supported by source and method triangulation to ensure trustworthiness. The findings reveal that the structured stages of Think–Pair–Share foster more equitable student participation, strengthen interpersonal communication and collaborative skills, and deepen contextual understanding of religious concepts. The Pair stage functions as a psychological bridge that reduces anxiety and increases students’ confidence before whole-class discussion. Conceptual understanding of riba evolved from normative definitions toward contextual application in everyday life. The novelty of this study lies in positioning Think–Pair–Share as a psychopedagogical mechanism that integrates cognitive and social development simultaneously in Islamic Religious Education. This study contributes theoretically to strengthening social constructivist perspectives in religious education and practically provides a structured interaction model for designing dialogical and context-responsive Islamic Religious Education learning at the vocational level.